The rising death burden of atrial fibrillation and flutter in low-income regions and younger populations - Liu, Ye-Mao; Wang, Wenxin; Zhang, Xingyuan; Lei, Fang; Qin, Juan-Juan; Huang, Xuewei; Li, Ruyan; Lin, Lijin; Chen, Mingming; Ji, Yan-Xiao; Zhang, Peng; Zhang, Xiao-Jing; et al. (Frontiers in Epidemiology, 2023)
Abstract Objective This study aimed to depict the global death burden of atrial fibrillation/flutter (AFF) from 1990 to 2019 and predict this burden in the next decade. Methods We retrieved annual death data on cases and rates of AFF between 1990 and 2019 from the Global Burden of Disease (GBD) Study 2019 and projected the trends from 2020 to 2029 by developing the Bayesian age-period-cohort (BAPC) model. Results The global number of deaths from AFF increased from 117038.00 in 1990 to 315336.80 in 2019. This number is projected to reach 404593.40 by 2029. The age-standardized mortality rates (ASMRs) of AFF have increased significantly in low- to middle- sociodemographic index (SDI) regions, which will surpass that in high SDI region and reach above 4.60 per 100,000 by 2029. Globally, women have a higher ASMR than men, which is largely attributed to disproportionately higher mortality in women than men in lower SDI regions. Notably, AFF-related premature mortality continues to worsen worldwide. A pandemic of high systolic blood pressure (SBP) and high body mass index (BMI) largely contributes to AFF-associated death. Particularly, low- to middle-SDI regions and younger populations are increasingly affected by the rapidly growing current and future risk of high BMI. Conclusion The global death burden of AFF in developing countries and younger generations have not been sufficiently controlled in the past and will continue growing in the future, which is largely attributed to metabolic risks, particularly to high BMI. There is an urgent need to implement effective measures to control AFF-related mortality.